2008
DOI: 10.1097/ypg.0b013e3282f97e0b
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of depressive symptoms in fragile-X syndrome premutated females

Abstract: Our findings reinforce the hypothesis of a pathogenic gene-brain-behavior mechanism in the premutation range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…Also, all the women with PPD but two experienced the lifetime onset of MDD in the postpartum period. Previous research has indicated higher depressive symptoms in mothers of children with FXS than in mothers of children with mental retardation due to another cause [23], as well as lower well-being levels in mothers of children with FXS [24]. Abbeduto et al showed a significant correlation between the number of disabled children and depressive symptoms in mothers of individuals with FXS, Down syndrome, and autism [24].…”
Section: Discussionmentioning
confidence: 99%
“…Also, all the women with PPD but two experienced the lifetime onset of MDD in the postpartum period. Previous research has indicated higher depressive symptoms in mothers of children with FXS than in mothers of children with mental retardation due to another cause [23], as well as lower well-being levels in mothers of children with FXS [24]. Abbeduto et al showed a significant correlation between the number of disabled children and depressive symptoms in mothers of individuals with FXS, Down syndrome, and autism [24].…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, it has been described that psychiatric symptoms, such as depression and anxiety, are often associated with fibromyalgia, 20,21 and interestingly, it has been shown that female premutation carriers have a distinctive neuropsychiatric profile with higher tendency to depression. 22,23 Taken together, the existence of these findings should be considered when offering genetic counseling for FXS, as they should be mentioned to premutation carriers. Although these disorders occur by a completely separate mechanism from FXS and affects different individuals, they are caused by defects in the same gene, therefore their study and characterization might help to better understand how the FMR1 gene works.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Riddle andco-workers (1998) andHagerman (2002) described a group of premutation carriers with prominent ears and joint laxity; or with learning disabilities, attention deficit/hyperactivity disorder (ADHD), or difficulty with math (Riddle et al, 1998, reviewed in Hagerman & Hagerman 2004). In addition, some carriers have emotional problems, including anxiety, obsessional thinking, schizotypy, and/or depression Rodriguez-Revenga et al, 2008a). Such findings were observed to be more likely to occur in carriers with a lowered FMRP levels and particularly in those carrier females with larger CGG expansions (>100 repeats) .…”
Section: Fragile X Syndrome Premutation and Fxtas Identificationmentioning
confidence: 56%